PKM PENANAMAN NILAI KARAKTER MELALUI MASA TAARUF SISWA MADRASAH DALAM KONDISI NORMAL BARU COVID-19 DI MA PLUS NURUL ISLAM SEKARBELA - Dedi Riyan Rizaldi; Muhamad Zaenudin; Fakhrurrozi Fakhrurrozi; Ziadatul Fatimah (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
Research has been carried out which aims to determine the implementation of introducing the madrasa environment to prospective new students through the activities of the Ta’aruf Period of Madrasah Students. This study uses a qualitative approach with the method of observation. This research was conducted on all prospective new students of MA Plus Nurul Islam Sekarbela for the academic year 2021/2022, with a total of 45 people. The implementation of the research went through two stages, namely the delivery of material and the introduction of the madrasa environment. Based on the results of observations and discussions, it can be seen that the activities of the Madrasah Student Ta’aruf Period are essential for prospective new students to get to know more about the conditions, characteristics, and environment of the madrasa. In addition, this activity instills various character values of madrasah children through various activities that are integrated with religious contexts to meet the goals set previously